Tracing the Evolution of Plant Glyoxalase III Enzymes for Structural and Functional Divergence - Brijesh Kumar; Charanpreet Kaur; Ashwani Pareek; Sudhir K. Sopory; Sneh L. Singla-Pareek (MDPI AG, 2021)
Glyoxalase pathway is the primary route for metabolism of methylglyoxal (MG), a toxic ubiquitous metabolite that affects redox homeostasis. It neutralizes MG using Glyoxalase I and Glyoxalase II (GLYI and GLYII) enzymes in the presence of reduced glutathione. In addition, there also exists a shorter route for the MG detoxification in the form of Glyoxalase III (GLYIII) enzymes, which can convert MG into D-lactate in a single-step without involving glutathione. GLYIII proteins in different systems demonstrate diverse functional capacities and play a vital role in oxidative stress response. To gain insight into their evolutionary patterns, here we studied the evolution of GLYIII enzymes across prokaryotes and eukaryotes, with special emphasis on plants. GLYIII proteins are characterized by the presence of DJ-1_PfpI domains thereby, belonging to the DJ-1_PfpI protein superfamily. Our analysis delineated evolution of double DJ-1_PfpI domains in plant GLYIII. Based on sequence and structural characteristics, plant GLYIII enzymes could be categorized into three different clusters, which followed different evolutionary trajectories. Importantly, GLYIII proteins from monocots and dicots group separately in each cluster and the each of the two domains of these proteins also cluster differentially. Overall, our findings suggested that GLYIII proteins have undergone significant evolutionary changes in plants, which is likely to confer diversity and flexibility in their functions.